Determinan kematian neonatal di Kabupaten Sintang Kalimantan Barat tahun 2022 - Arum Seftiani Lestari; Siswanto Pabidang; Heru Subaris Kasjono; Atik Ba'diah; Yolanda Montessori; Rizki Amartani (Politeknik Kesehatan Kemenkes Aceh, 2023)
Background: Neonatal mortality is an indicator to take a look at the degree of public health because health progress is seen from the seriousness of all elements of society in reducing neonatal mortality. 2017 Indonesian Demographic and Health Survey (IDHS) showed that 15/1,000 live births occurred during the neonatal period. This research was conducted to analyze the determinants of neonatal mortality in the Sintang district in 2022.Objective: To analyze what are the determinants that affect neonatal mortality in Sintang District, West Kalimantan 2022.Methods: Mix method research with sequential explanatory design. Beginning with a descriptive quantitative research design by looking at medical record data, followed by qualitative research in the form of in-depth interviews. which combines quantitative and qualitative. Quantitative research samples totaled 52 cases and qualitative samples totaled 11 informants. Research time October to November 2022.Results: The quantitative results of the near determinant of neonatal mortality were asphyxia at 44,2% and premature at 19,2%, the intermediate determinant was due to maternal age at 61,5%, and gestational age at 53,8%, the determinant of distance was due to ANC examination 36,5% and the distance house 30.8%. The qualitative results of the determinants of distance are irregular ANC, delivery assistance by non-medical personnel, place of delivery without health facilities, and distance from home to health facilities, intermediate determinants are the age of at-risk mothers, high parity, a distance of at-risk pregnancies and complications of pregnancy and childbirth, determinants of near-death neonatal are asphyxia, premature and pneumonia.Conclusion: Causes of neonatal mortality in Sintang District occur from close determinants (asphyxia and premature), intermediate determinants (age of mother and gestation), and distant determinants (ANC examination and distance from home).